Sistem Informasi Pengajuan Cuti Karyawan Pada Pt.Tass Engginering Berbasis Website - Donny Maulana; Emilda Yulian Sari (DPPM Universitas Pelita Bangsa, 2025)
The rapid development of information technology encourages companies to implement web-based information systems to improve the effectiveness and efficiency of data management. PT Tass Engineering still manages employee leave requests manually using paper forms and simple office applications, which often leads to recording errors, delays in approval processes, and potential data loss. This study aims to design and develop a web-based Employee Leave Management Information System that facilitates the submission, approval, and management of leave data in an integrated manner. The research method uses structured interviews to identify system requirements, while the system development applies the Waterfall model, consisting of requirement analysis, system design, implementation, testing, and maintenance stages. The system is modeled using Unified Modeling Language (UML) and implemented using PHP as the programming language and MySQL as the database, running on a XAMPP environment. System testing is conducted using the Black Box Testing method to ensure that each function operates according to the specified requirements. The results indicate that key features, including login authentication, leave submission, employee data management, approval processes, and report generation, function properly and meet user needs. The developed system improves administrative efficiency, minimizes human error, and ensures centralized and secure data storage within the database.